Traços da Libras no papel e na memória - Freitas, Isaac Figueredo de (2021)
This dissertation is the result of a doctoral study that investigated the possible metalinguistic and evocative potential of Sutton orthography (SignWriting) in non-deaf adult people beginning to learn Libras (Brazilian Sign Language) as a second language in the process of recovering lexical and syntactic components. It takes Psycholinguistics as an interdisciplinary theoretical articulator, which ramifies dialogs with Applied Linguistics, Descriptive Linguistics, and Cognitive Psychology, notably in theories related to memory and evocation. As for the methodology, it is a study with experimental data collection through two experiments: a lexical evocation experiment focusing on Libras’ symmetrical and asymmetrical bimanual signs, which had four subjects in the Control Group and five in the Experimental Group; and a syntactic structure evocation experiment focusing on the surface structures of Wh- questions and Yes/No polar sentences, which had two subjects in the Control Group and five in the Experimental Group. In both experiments, verbal evocation tips were used in gloss format—for the Control Group—or in Sutton orthography—for the Experimental Group. The analyzed data suggested that the Sutton orthography had evocative and metalinguistic potential in the researched learners. Furthermore, Sutton writing seemed to favor the evocation of symmetrical bimanual signs with simultaneous movement, while glossing writing seemed to favor the evocation of asymmetrical bimanual signs. Additionally, learners exposed to Sutton writing presented a repeated behavior of graphemic decipherment attempts during the lexical evocation experiment, something that did not occur in the Control Group, a possible indication that this writing stimulated the phonemic awareness of the participants. The results of the syntactic structure evocation experiment evidenced that the surface structures of the Yes/No polar interrogative sentences seemed to take longer to be read, with a shorter time to recover Wh- questions; however, it was not possible to outline a reliable statistical trend in this finding. Furthermore, the participants in the Experimental Group evoked interrogative syntactic structures compatible with 14 interrogative sentences—7 of the Yes/No type and 7 of the Wh- type—out of a total of 20 sentences that could be evoked. This finding seems consistent in indicating the potential of Sutton orthography in providing Libras learners in this study with the recovery of interrogative syntactic structures from surface textual clues. However, caution should be aken due to the small number of participants in the experiments conducted in this study, as the numerical data obtained do not allow definitive conclusions nor the outline of statistical trends with generalizable results. This gives rise to the need for more comprehensive studies, perhaps longitudinal in nature, with a quantitatively more representative sample.